Gender differences in the effects of competition and cooperation on risk‐taking under ambiguity. Issue 3 (21st December 2020) - Liu, Zhenliang; Liu, Tiantian; Mu, Shoukuan
Abstract: Decision theories have made a distinction between risk (i.e., known probabilities) and ambiguity (i.e., unknown probabilities). Prior work has examined the effect of competition and cooperation on risk‐taking under risk. However, little is known about whether and how competition and cooperation affect risk‐taking under ambiguity and the role of gender in this effect. The current study addresses this research gap. In the present study, a shortened version of a balloon analogue risk task was used to assess risk‐taking under ambiguity. The participants completed this task in competition against a peer, in cooperation with a peer, or alone. The results showed that the participants took more risks in the competition and cooperation conditions than in the individual condition, but no differences were found between the competition and cooperation conditions. More important, gender modulated these effects. First, these effects were driven by males, but not by females. Second, males showed more risk‐taking under ambiguity than females in the competitive situation, but not in the cooperative situation. Overall, this work contributes to understanding the effect of social interaction on risky decisions under ambiguity.